1971
DOI: 10.1104/pp.47.5.600
|View full text |Cite
|
Sign up to set email alerts
|

Spectral, Physical, and Electron Transport Activities in the Photosynthetic Apparatus of Mesophyll Cells and Bundle Sheath Cells of Digitaria sanguinalis (L.) Scop.

Abstract: Isolated mesophyll cells and bundle sheath cells of Digitaria sanguinalis were used to study the light-absorbing pigments and electron transport reactions of a plant which possesses the C4-dicarboxylic acid cycle of photosynthesis. Absorption spectra and chlorophyll determinations are presented showing that mesophyll cells have a chlorophyll a-b ratio of about 3.0 and bundle sheath cells have a chlorophyll a-b ratio of about 4.5.The absorption spectrum of bundle sheath cells has a greater absorption in the 700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
13
0

Year Published

1972
1972
1978
1978

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In bundle sheath cells of Digitaria, relatively high rates of 02 evolution have been observed with benzoquinone as the electron acceptor (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In bundle sheath cells of Digitaria, relatively high rates of 02 evolution have been observed with benzoquinone as the electron acceptor (23).…”
mentioning
confidence: 99%
“…On the basis of its higher P700 content (3,23) or saturation intensity (27), it has been suggested that the photosynthetic unit is smaller in bundle sheath than in mesophyll cells.…”
mentioning
confidence: 99%
“…The entire electron transport chain is shown to be present in both types of chloroplasts, as inferred from the antagonistic effect of red (650 nm pending on the species, age, and growth conditions. Several papers have been published on the photochemical activities of the two types of chloroplasts (2,5,20,24). In spite of some of the controversial reports, it is now clear that BS Chip2 are enriched in PS I relative to PS II: there is about 3-fold higher PS I/PS II ratio in these chloroplasts than in M Chlp.…”
mentioning
confidence: 99%
“…Vol. 50,1972 pH DEPENDENCE OF PHOTOCHEMICAL REACTIONS ously reported for maize (5,15), Sorghum bicolor (15), and Digitaria sanguinalis (11). Maximum photosystem I activity of both mesophyll and bundle sheath chloroplasts is obtained in a sonicated preparation supplemented with plastocyanin and ferredoxin reductase, but on a chlorophyll basis, the activity of the bundle sheath chloroplasts is twice that of the mesophyll chloroplasts.…”
mentioning
confidence: 93%